"The Cat's Paw of Dictatorship": Police Intelligence and Self-Rule in the Gold Coast, 1948–1952. Issue 2 (2nd April 2020) - Arnold, Chase
ABSTRACT: In 1948, British authorities in the Gold Coast implemented a series of security reforms aimed at resisting future disruptions resulting from growing discontent with colonial rule. These reforms included the formation of a police intelligence organization, developed in collaboration with the British Security Service. This expansion of the colonial state into intelligence work preceded its first steps toward self-rule, inadvertently making this intelligence program an unintended participant in the process of decolonization. This article examines the foundations of that intelligence network and how it resisted the political exigencies required by the Gold Coast's entry into diarchy. It explains how British officials arrived at the conclusion that a West African colony required a modern, intelligence-gathering apparatus under the oversight of the British Security Service and how that security system was used to challenge the realization of an independent Ghanaian state under the leadership of Kwame Nkrumah.